Formulation Strategy of PT. Bandara Internasional Jawa Barat Bandung Indonesia, Kertajati in Business Aerocity (Aerotropolis) - Syafarudin, Afriapollo; Mulyana, Bambang (International Review of Management and Marketing, 2019)
Aerotropolis is a city airport development concept, or commonly called "Airport City". The concept of Aerotropolis is a new concept in the world transport industry where the Airport has shifted from transportation center to a multifunctional aero metropolis. The development of an international airport can be a trigger for business development as well as the surrounding urban areas. The airport city serves not only as a performance index of a State in development but also plays a role as a driver of national industry and the gateway to economic globalization. Through library reviews, secondary data analysis and interviews with focus groups and experts, this paper explores the development features, operating strategies and competitive advantages of the Aerogity Business concept at Kertajati International Airport. This research proposes the formulation of strategy based on resource-based approach and also using approach of strategy formulation of Wheelen and Hunger model in which there is analysis of external factor evaluation, internal factor evaluation, then determining strategic direction by using TOWS matrix. Case study at Kertajati International Airport which carries Aerotropolis concept in accordance with master plan of Airport development. The proposed strategic plan is expected to provide a systematic referral of operations for PT. BIJB as the International Airport Company Kertajati as well as Aerocity Business Company, but it is also expected to inspire for new research in the framework of study for the development of Airport City in Indonesia. Keywords: Aerocity, Swot analysis, Strategy formulation, Development and Evaluation JEL Classification: L1 DOI: https://doi.org/10.32479/irmm.8113